2017
DOI: 10.1016/j.celrep.2017.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Roles for Cell-Cell Adhesion and Contact in Obesity-Induced Hepatic Myeloid Cell Accumulation and Glucose Intolerance

Abstract: Obesity promotes infiltration of inflammatory cells into various tissues, leading to parenchymal and stromal cell interaction and development of cellular and organ dysfunction. Liver sinusoidal endothelial cells (LSECs) are the first cells that contact portal blood cells and substances in the liver, but their functions in the development of obesity-associated glucose metabolism remain unclear. Here, we find that LSECs are involved in obesity-associated accumulation of myeloid cells via VLA-4-dependent cell-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 45 publications
2
55
0
Order By: Relevance
“…KC depletion by clodronate suppresses the infiltration of monocytes into the liver, potentially due to decreased CCL2 release (53,66); however, these studies are challenging to interpret as clodrolip also depletes monocytes directly. Liver sinusoidal endothelial cells also upregulate VCAM-1 in response to inflammation thereby facilitating adhesion of monocytes (67). Related to this, it has been reported that under lipotoxic stress hepatocytes release extracellular vesicles which are enriched with the integrin ITGβ 1 , a VCAM-1 ligand, which subsequently enhances monocyte adhesion to sinusoidal endothelial cells (68).…”
Section: Macrophages In Obesity and Nafldmentioning
confidence: 91%
“…KC depletion by clodronate suppresses the infiltration of monocytes into the liver, potentially due to decreased CCL2 release (53,66); however, these studies are challenging to interpret as clodrolip also depletes monocytes directly. Liver sinusoidal endothelial cells also upregulate VCAM-1 in response to inflammation thereby facilitating adhesion of monocytes (67). Related to this, it has been reported that under lipotoxic stress hepatocytes release extracellular vesicles which are enriched with the integrin ITGβ 1 , a VCAM-1 ligand, which subsequently enhances monocyte adhesion to sinusoidal endothelial cells (68).…”
Section: Macrophages In Obesity and Nafldmentioning
confidence: 91%
“…Total RNA was extracted using Qiazol (QIAGEN). cDNA synthesis and quantitative real-time polymerase chain reaction (PCR) were performed as described previously 16 .…”
Section: Methodsmentioning
confidence: 99%
“…The latter respond to inflammation or lipid accumulation by upregulating leukocyte adhesion molecules and facilitating VCAM-1/very late antigen-4 (VLA-4)dependent monocyte adhesion and migration. 118 Nevertheless, other chemokine pathways have been identified that also regulate myeloid cell recruitment, including CCL25/CCR9 and CCL1/ CCR8. 119,120 The recruitment of infiltrating monocytederived macrophages is also observed in human fatty liver disease, especially in patients with more advanced stages of fibrosis, where these cells accumulate mainly in clusters around the portal areas.…”
Section: Inflammatory Macrophages Drive Nonalcoholic Fatty Liver Disementioning
confidence: 99%